Karakter Morfologi Talas (Colocasia Esculenta) Sebagai Indikator Level Kadar Oksalat Menggunakan Lensa Makro - Wahyu Safriansyah; Asman Asman; Nur Azizah Ferdiana; Atiek Rostika Noviyanti (Jambura Journal of Chemistry, 2021)
Taro plant (Colocasia esculenta) is a type of tuber that contains many useful compounds, less fat and lots of vitamin A. The high calcium oxalate content in taro is an anti-nutritional and toxic which can cause itching in the mouth, burning sensation, irritation of the skin, mouth, and digestive tract. Taro processing reduced its oxalate levels, which also influenced the morphological changes observed by Scanning Electron Microscopy SEM imaging. There is no practical way to predict the oxalate level of taro, making it easier to predict its toxicity. The purpose of this study is to predict the level of taro toxicity based on its morphology using a more practical tool such as a macro lens combined with a smartphone. The prediction of oxalate levels in taro was carried out by combining taro morphological data based on SEM and several object images produced by a macro lens equipped with a smartphone. The image of the object captured with a macro lens is supplemented with a fluorescent procedure to enhance the sharpness of the image. The prediction of oxalate levels in taro using a macro lens is distinguished based on the number of dark sides (dots) in the imaging results. The accuracy of macro lenses is of course lower than SEM, but at least the results are used as an initial prediction of oxalate levels in taro.